Who is responsible for postpartum contraception advice and provision? The perspective of hospital-based maternity clinicians in NSW, Australia. (September 2022) - Botfield, Jessica; Tulloch, Melanie; Contziu, Hannah; Bateson, Deborah; Phipps, Hala; Wright, Sarah; McGeechan, Kevin; Black, Kirsten
Abstract : Background: Many pregnancies in the first year after a birth are not intended. Access to postpartum contraception is critical for the health of the mother and subsequent pregnancies. In many maternity settings in Australia, the roles and responsibilities of maternity care providers (including midwives, obstetricians and general practitioners) in providing postpartum contraception information and services is not always clear, and there is no consistent system or process to ensure timely access. Objective: We undertook an analysis of interview data conducted with hospital-based maternity clinicians as part of a larger study on midwifery provision of contraceptive implants in New South Wales, Australia, to document their views regarding access to postpartum contraception and clinician responsibilities. Methods: Interviews were conducted with maternity hospital clinicians (midwives, doctors, midwifery managers and clinical midwifery specialists) in two hospitals. Reflexive thematic analysis was used for the analysis of interview data. Themes relating to postpartum contraception access, timing of contraceptive discussions and the role of clinicians were identified. Results: Interviews were conducted with 21 hospital-based maternity clinicians. Participants suggested contraception discussions and provision are a shared responsibility by maternity care providers but identified inconsistencies and issues with current approaches. Ensuring postpartum contraception was accessible in hospital, primary care and community settings was raised. Conclusion: Postpartum contraception discussions and provision are regarded as a shared responsibility by maternity care providers. This would ideally be led by the primary provider. These services are not routinely available or always easily accessible in Australian maternity care settings, however, and there is a lack of consistency in how postpartum contraception is managed. Access to postpartum contraception could be improved through routine inclusion of contraception discussions during antenatal and postpartum care, and greater collaboration between maternity care providers in hospital, community and primary care settings to support continuity of care through the postpartum period.